Indikasi Ketidakstabilan Harga terhadap Elastisitas Permintaan Minyak Goreng Kemasan dan Minyak Goreng Curah di Pasar Ciawitali Garut - Yayu Yunengsih Rahayu; Mudrika Mudrika; De Dita Nur Padilah; Ryan Ahmad Zaelani; Ira Murwenie (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the effect of the price of packaged cooking oil and bulk cooking oil on the elasticity of demand as one of the staple foods in Ciawitali Market, Garut Regency. The approach used is a quantitative descriptive method with a focus on associative analysis. Data were collected through observation and interviews in the period of September and October 2025. Then processed using simple linear regression analysis and demand elasticity analysis. The results show that the demand for both types of cooking oil is strongly influenced by price. For packaged cooking oil, it shows that 81.6% of the variation is influenced by price while the rest is influenced by other factors. For bulk cooking oil, it shows that 94.1% is influenced by price with an elasticity value of -6.346, which also shows elastic properties but lower than packaged oil which has an elasticity of -22.15. These results indicate that the increase in the price of packaged and bulk oil significantly reduces the amount of demand, with the greatest effect occurring on packaged oil because consumers tend to switch to more economical bulk oil.